Management of Ciamis Type C Terminal from a good Governance Perspective by the Regional Technical Implementation Unit (UPTD) of the Ciamis Regency Transportation Office - Aldzikri Sulaksana; Neti Sunarti; Ii Sujai (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract This study examines the terminal governance of Type C Ciamis Terminal from the perspective of Good Governance by the Regional Technical Implementation Unit (UPTD) of the Ciamis Regency Transportation Agency. Terminal management faces significant challenges, including a decrease in public transportation passengers, a lack of public environmental awareness regarding waste management, and suboptimal infrastructure maintenance. This research employs a descriptive qualitative method. Data collection was carried out through structured observations, semi-structured interviews with 7 informants (including head of UPTD, head of administrative subdivision, general administration officer, drivers, and local traders), and official documentation analysis. The findings indicate that while several dimensions such as participation, law enforcement, equity, effectiveness, and accountability have been successfully operationalized, four key indicators remain suboptimal: transparency in information disclosure regarding regional non-tax revenues, active physical complaint mechanisms, sustainable institutional coordination, and a clear infrastructure modernization policy framework. Thus, structured improvements are required to elevate public services quality. Keywords: Governance, Good Governance, Type C Terminal, Public Transportation, UPTD Dishub